La diffusion spatiale de l’informatique en Inde - Divya Leducq (EchoGéo)
India is an emergent superpower which asserts itself through outsourced services, the so-called “IT industry”. Beyond the fact that InfoTech are seen as a trickle-down development engine, it is the cluster which has become gradually a town planning measure in the sectoral policies followed by the central government and the regional states. The diffusion of this spatial model can be explained by the success stories which made the reputation of India and the expected benefits in terms of innovation. This article analyzes the successive strategies of development based on IT clusters through a geographical and economical prism. The role of the scales and of the actors will be emphasized, while resting on the specific instance of the Kerala state.